Effects of using different levels of dietary chitosan on some immune indices and antioxidant defense system in Vannamei shrimp, Litopenaeus vannamei - Saeed Dayani; Valiallah Jafari; Roghayeh Safari; Seyed Hossein Hoseinifar (تغذیه آبزیان)
Introduction: Aquaculture aims to provide stable environmental conditions for fish to be able to grow and protect it from stress and diseases. To guarantee a sustainable yield of fish species, well-balanced diets should be considered. For this purpose, diets supplemented with feed additives have won the interest of researchers who are concerned with the aquaculture field, the most important of which is chitosan, a cationic biopolymer, derived from the alkaline deacetylation of chitin; a natural polymer found in the exoskeletons of insects, crustaceans and fungal cell walls. Therefore, the purpose of this study was to examine the effects of using dietary chitosan in some immune indices and antioxidant defence system in Vannamei shrimp, Litopenaeus vannamei. Materials and Methods: For this purpose, 180 pieces of Vannamei shrimp with an average weight of about 4 g were prepared and kept for 2 weeks to adapt to the test conditions. We prepared 4 groups, each with three repetitions, including the basal diet of zero (control), 1 g (treatment 1 = T1), 2 g (T2) and 4 g (T3) chitosan per kilogram of feed in a completely randomized design for 8 weeks. At the end of the trial, samples were randomly taken from the rearing tanks and hemolymph indices including serum biochemical, immune and antioxidant indices were measured. Results and Discussion: According to the results, immune indices such as lysozyme and immunoglobulin increased significantly compared to the control group (p<0.05). So that in case of lysozyme, the highest amount was recorded in T2 (by adding 2 g/kg chitosan), while in immunoglobulin, the highest amount was observed in T1. Serum antioxidant activity such as superoxide dismutase (in T1 and T2) and catalase (in T1, T2 and T3) increased significantly compared to the control group (p<0.05). Also, the results of the serum biochemical analyses exhibited that only ALP enzyme recorded a significant difference (p<0.05), so that the highest value was observed in T3. According to the results, there was no significant difference (p>0.05) in ALT and AST enzymes among treatments. So that the highest amounts of these two enzymes were observed in T2 and the control group, respectively. Conclusion:  The results of this study indicate the positive effects of chitosan on immune indices in Vannamei shrimp. Therefore, it is possible to recommend using chitosan as a natural and immune stimulant for culture of L. vannamei.